Análise de viabilidade do processo de laser cladding para a recuperação de eixos de transmissão em equipamentos de grande porte - Lorenzoni, Marco Gabriel (2023)
Large-scale gearboxes’ shafts are high-value-added components. In situations where these parts experience superficial wear, a cost-effective solution is the recovery of the damaged region through additive manufacturing processes, particularly laser cladding. Generally, high cooling rates are generated during this operation. They bring benefits such as increased surface hardness of the region and grain refinement, but they also promote the accumulation of thermal stresses in the coating and alteration of the microstructure in the substrate. When these stresses exceed the tensile strength limit of the coating material, it is highly likely that cracks will form in its structure. The most recommended solution to prevent the formation of defects in the coating is preheating the substrate. With this strategy, it is possible to reduce the thermal stresses induced in the process, provide a more homogeneous microstructure to the coating, improve its surface finish, and prevent crack formation in its structure. On the other hand, preheating temperatures can impact the properties of critical regions of the part, such as the surface hardness of the teeth. In pinions and gears, the surface hardness of the teeth is a very important characteristic to ensure their durability. The quality of the coating and control over residual stresses induced in the substrate are essential for the operational reliability of the equipment after the repair. This work presents a study on preheating and deposition parameters aiming to enable the recovery, through the laser cladding process, of shaft necks of large-scale gearboxes’ pinions made of 18CrNiMo7- 6 alloy steel. Following the preheating recommendations for welding according to the equivalent carbon rule, a temperature of 250°C was defined for preheating the region of the shaft to be recovered (50°C above the tempering temperature of the teeth). A preliminary experiment of shaft preheating with a torch was performed to define the input data for the computational model. Through numerical simulation, using the three-dimensional model of the shaft and the finite element method, it was possible to conclude that preheating at 250°C does not compromise the mechanical properties of the teeth. To evaluate the quality of the coating generated with this preheating temperature, the deposition of the HGMET metallic powder alloy was performed on two samples of DIN 18CrNiMo7-6 steel through the laser cladding process. The samples were processed with different preheating parameters and laser power (sample 1: 250°C and 3 kW; sample 2: 400°C and 4 kW). Sample 2 showed good structural integrity of the coating, while severe cracks formed in sample 1. It is concluded that in order to ensure the quality of HGMET coatings deposited by laser cladding on 18CrNiMo7-6 alloy steel substrate, preheating at temperatures around 400°C is necessary, which makes the recovery process infeasible for some regions of the shaft as it affects the surface hardness of the teeth